Design and Analysis of Engine-Generator Assembly for C-Drone - Cheng Yong, Tan; Alimin, Ahmad Jais (Research Progress in Mechanical and Manufacturing Engineering, 2021)
C-Drone is a cargo drone which is expected to handle the payload up to 180kg and cruise up to two hours. However, the C-Drone can only travel for five minutes when the batteries are fully charged. Hence, the purpose of this project is to design and analyse the PCD adapter and boom structure that unite the components as an Engine-generator Assembly which can act as powerplant to charge the C-Drone batteries continuously. By referring to the engineering design process the components for the Engine-generator Assembly are generated. The PCD adapter is designed based on the concept of jaws coupling and the components for PCD adapter are spacer shaft, jaws coupling insert and engine coupling. The material for the spacer shaft is AISI 303 Stainless Steel and Aluminium Alloy-6063 for the engine coupling. Nitrile Butadiene Rubber (NBR) jaws coupling insert is used intermediate between spacer shaft and engine coupling. The overall mass of PCD adapter is 3.803kg. Furthermore, boom structure with high strength and light weight is designed through idea of sheet metal bending to fabricate the subframe. The material used for both boom and subframe are AISI 4140 alloy steel and the mass of boom and subframe are 2.908kg and 1.874kg respectively. Based on the result obtained from simulation analysis, the PCD adapter and boom structure achieved minimum safety factor of 18.829 and 2.936 respectively. Which indicates that the PCD adapter can transmit the torque of 150